Perceptual experience shapes our ability to categorize faces by national origin: A new other‐race effect. (23rd February 2018) - Thorup, Bianca; Crookes, Kate; Chang, Paul P. W.; Burton, Nichola; Pond, Stephen; Li, Tze Kwan; Hsiao, Janet; Rhodes, Gillian
Abstract : People are better at recognizing own‐race than other‐race faces. This other‐race effect has been argued to be the result of perceptual expertise, whereby face‐specific perceptual mechanisms are tuned through experience. We designed new tasks to determine whether other‐race effects extend to categorizing faces by national origin. We began by selecting sets of face stimuli for these tasks that are typical in appearance for each of six nations (three Caucasian, three Asian) according to people from those nations (Study 1). Caucasian and Asian participants then categorized these faces by national origin (Study 2). Own‐race faces were categorized more accurately than other‐race faces. In contrast, Asian American participants, with more extensive other‐race experience than the first Asian group, categorized other‐race faces better than own‐race faces, demonstrating a reversal of the other‐race effect. Therefore, other‐race effects extend to the ability to categorize faces by national origin, but only if participants have greater perceptual experience with own‐race, than other‐race faces. Study 3 ruled out non‐perceptual accounts by showing that Caucasian and Asian faces were sorted more accurately by own‐race than other‐race participants, even in a sorting task without any explicit labelling required. Together, our results demonstrate a new other‐race effect in sensitivity to national origin of faces that is linked to perceptual expertise.